Innovations in Non-Destructive Testing of Railway Freight Wagon Wheelset Axles (Current Problems in Rail Vehicles, 2025)
The article focuses on the diagnostics of railway freight wagon wheelset axles in terms of non-destructive testing within maintenance. It describes the current standard approach, including the advantages and risks that led to the research and development of a new testing device.
Keywords: wheelset axle; non-destructive testing; eddy current testing; testing device